Environmental change and the informal plastic recycling networks of Kolkata. Issue 3 (26th May 2020) - Schlitz, Nicolas
Abstract : This article introduces plastic recycling networks in Kolkata, India, as a case to illustrate the contradictory entanglement of economic and environmental change in urban informal contexts of the Global South. In light of the prevailing environmental critique of informal plastic recycling in India, this article discusses plastic recyclers' environmental impact and contribution as well as the potential to enhance the environmental and economic performance of their business. Network and chain approaches in the emerging field of Environmental Economic Geography are combined with the notion of social metabolism to conceptualize the entanglement of environmental and economic processes as well as socio‐environmental inequalities entailed in recycling networks. The analysis reveals the impact that the heterogeneity and fluctuation of plastic waste supply has on the economic organization of recycling networks, giving rise to distinct forms of governance in its intermediate and down‐stream segments. Such an integrated perspective also serves to explain why environmental upgrading is hard to achieve under prevailing circumstances by plastic recyclers in Kolkata. Based on an assessment of the social and political conditions of informality under which plastic recyclers operate, the adoption of common assumptions about ecological modernization imbuing parts of Environmental Economic Geography is called into question.